1988
DOI: 10.3109/01050398809042189
|View full text |Cite
|
Sign up to set email alerts
|

Low-Frequency Auditory Brainstem Response Threshold

Abstract: Auditory brainstem thresholds have been determined in 35 non-cooperative, anaesthetized children using a 'two-point audiogram' paradigm. The high-frequency point was found with a 2 kHz tone-burst without masking, and the low-frequency with a 0.5 kHz tone-burst together with 1 kHz high-pass noise masking. Great variability was found in the low-frequency thresholds, and only 3 of 18 ears with normal high-frequency thresholds had low-frequency thresholds below 70 dB nHL. It is concluded that the 0.5 kHz tone-burs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 33 publications
2
12
0
Order By: Relevance
“…[50][51][52] Controversy exists about the frequency specificity of lowfrequency TS, and the evoked responses are different from those of CS-evoked responses. Low-frequency testing has been performed in dogs and cats by TS of 1 kHz or less.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[50][51][52] Controversy exists about the frequency specificity of lowfrequency TS, and the evoked responses are different from those of CS-evoked responses. Low-frequency testing has been performed in dogs and cats by TS of 1 kHz or less.…”
Section: Discussionmentioning
confidence: 99%
“…Low-frequency testing has been performed in dogs and cats by TS of 1 kHz or less. 24,51,53 The responses were reported to be FFRs, which are short-latency scalp-recorded evoked potentials elicited by the presentation of low-frequency acoustic stimuli. They are ascribed to the electrical activity in brainstem auditory nuclei synchronous with each wave in the acoustic signal.…”
Section: Discussionmentioning
confidence: 99%
“…These studies 7,9 contain few subjects that have electrophysiological thresholds below 70 dBHL, suggesting that the clinical use of tone bursts is questionable.…”
Section: Introductionmentioning
confidence: 99%
“…There are many studies related to hearing thresholds successfully identified by using ABRs [3,4,16,17] . Research conducted on infants and children with normal hearing and sensorineural hearing loss has shown a high correlation between pure tone hearing thresholds and tone-burst ABR results [15] .…”
Section: Discussionmentioning
confidence: 99%